My first Menorah - Yoon, Salina (New York, N.Y. : Little Simon, 2005)
Hanukkah miracles fill the pages of this sparkly foil menorah book! Turn the candle-shaped pages one by one to learn about the eight days of this Jewish holiday and celebrate with blessings, gifts, and family fun.
Cover title.
On board pages.
Keywords: Hanukkah -- Juvenile literature